2014
DOI: 10.1038/jes.2014.56
|View full text |Cite
|
Sign up to set email alerts
|

Personal particulate matter exposures and locations of students in four neighborhoods in Accra, Ghana

Abstract: Air pollution exposure and places where the exposures occur may differ in cities in the developing world compared with high-income countries. Our aim was to measure personal fine particulate matter (PM2.5) exposure of students in neighborhoods of varying socioeconomic status in Accra, Ghana, and to quantify the main predictors of exposure. We measured 24-hour PM2.5 exposure of 56 students from eight schools in four neighborhoods. PM2.5 was measured both gravimetrically and continuously, with time-matched globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…This difference was explained by participants' activities during the day, which resulted in higher levels of exposure compared to background PM 2.5 . Similar results have been found in lowmiddle income countries comparing personal and ambient PM 2.5 11,38 . Comparable levels of personal and ambient PM 2.5 at night were likely due to well ventilated buildings and the lack of indoor sources at night.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This difference was explained by participants' activities during the day, which resulted in higher levels of exposure compared to background PM 2.5 . Similar results have been found in lowmiddle income countries comparing personal and ambient PM 2.5 11,38 . Comparable levels of personal and ambient PM 2.5 at night were likely due to well ventilated buildings and the lack of indoor sources at night.…”
Section: Discussionsupporting
confidence: 88%
“…As a comparison, a study that measured 62 non-smoking pregnant women in Canada in 1-3 48h monitoring sessions42 developed a prediction model for personal exposure to fine particulate matter with a selfreported diary of activities and locations and ambient monitoring which explained a 29% of the exposure variability. In another study measuring 56 students from eight schools in Ghana, models predicting 24h personal exposure to PM 2.5 using fixed household indicators as well as ambient concentrations, meteorology, and GPS-derived distance from several sources during the day, achieved a conditional R 2 of 0.6211 . Finally, a study on 200 women cooking with biomass fuels in Sichuan, China, explained 52% of the variability of 48h PM 2.5 exposure in…”
mentioning
confidence: 99%
“…It was 4.7 times the daily average PE PM 2.5 concentration in dry and wet seasons (331.7 ± 190.7 µg m −3 ). Student (10-17 years old) PM 2.5 exposures ranged from less than 10 µg m −3 to more than 150 µg m −3 (mean 56 µg m −3 ) in four neighborhoods in Accra, Ghana (Arku et al, 2015), much lower than that for students at the WB site (356.9 ± 71.9 µg m −3 ). It can be seen that the high PM 2.5 exposure of students in this study was likely related to waste burning emissions, while there was no obvious strong PM 2.5 emission source in the study of Arku et al (2015).…”
Section: Mass Concentrationmentioning
confidence: 81%
“…That study reported average personal exposure to BC of 8.8 µg/m 3 and average cooking area BC of 14.5 µg/m 3 . Arku et al (2015) performed personal PM 2.5 sampling in Accra, the national capital located along the coast in Southern Ghana, as part of a 'spatial sources and exposure' study. That work found average PM 2.5 mass concentrations of 56 µg/m 3 , with differences in exposure based on gender and neighborhood affluence.…”
Section: Relevant Previous Workmentioning
confidence: 99%
“…Summary statistics for the EC, OC, and organics are shown separately for personal and microenvironmental samples in The observed average PM 2.5 personal exposures in REACCTING appear lower than comparable previous works, although it must be emphasized that here the sum of EC and OC is reported, while the following works used total gravimetric PM 2.5 mass. In Ghana, personal PM 2.5 sampling was performed on high school students in Accra, Ghana, (Arku et al, 2015), where they found average 24-h concentrations of 56 µg/m 3…”
Section: Personal Carbonaceous Pm 25mentioning
confidence: 99%